2016
DOI: 10.21037/jgo.2016.09.01
|View full text |Cite
|
Sign up to set email alerts
|

Molecular profiling of biliary tract cancer: a target rich disease

Abstract: Biliary tract cancers (BTCs) are relatively uncommon orphan tumors that have an aggressive disease course and a poor clinical outcome. Surgery is the only curative treatment, but most patients present with advanced disease and therefore have a limited survival. Gemcitabine and cisplatin based chemotherapy has been the only widely accepted standard systemic therapy regimen in these patients but these tumors can be chemoresistant, further complicating their management. In recent times, there has been considerabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
71
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(81 citation statements)
references
References 48 publications
(57 reference statements)
3
71
1
Order By: Relevance
“…Performing randomized control trials (RCT) for advanced BTCs has proven challenging due to the rarity of these malignancies, lack of effective agents, potential high heterogeneity within this diagnostic entity, and possibly fundamental differences among the three BTC subtypes (IHCC, EHCC, and GBC). In fact, next generation sequencing (NGS) and transcriptomic analyses have revealed that these BTC subtypes are molecularly distinct from one another, and therefore may respond differently to the same treatment strategy and should not be approached as a single entity for clinical trial design (13,14). To improve patient outcome, future clinical trial design must better stratify patients based on considerations of histologic and molecular subtypes, and allocate patients to the appropriate targeted agents driven by biomarkers that could predict treatment response.…”
Section: Current Managementmentioning
confidence: 99%
“…Performing randomized control trials (RCT) for advanced BTCs has proven challenging due to the rarity of these malignancies, lack of effective agents, potential high heterogeneity within this diagnostic entity, and possibly fundamental differences among the three BTC subtypes (IHCC, EHCC, and GBC). In fact, next generation sequencing (NGS) and transcriptomic analyses have revealed that these BTC subtypes are molecularly distinct from one another, and therefore may respond differently to the same treatment strategy and should not be approached as a single entity for clinical trial design (13,14). To improve patient outcome, future clinical trial design must better stratify patients based on considerations of histologic and molecular subtypes, and allocate patients to the appropriate targeted agents driven by biomarkers that could predict treatment response.…”
Section: Current Managementmentioning
confidence: 99%
“…Since the prognosis of CCA remains poor with traditional chemotherapy, in the era of personalized medicine several research teams have been working on the molecular and genetic characterization of CCA to identify molecular targets (5)(6)(7)(8)14). Landscape of signalling pathways offers multiple therapeutic targets including growth factor receptors (GFRs) like epidermal (EGFR), vascular (VEGFR), human epidermal growth factor receptor 2 (HER2), the ligand of VEGFR (VEGF) and their downstreaming signal molecules of RAS-RAF-MEK-ERK and PI3K-ACT-mTOR (5)(6)(7)(8)14). Targetspecific monoclonal antibodies and tyrosine kinase inhibitors are able to block selectively the over-expressed or over-activated signal molecules potentiating the growth and invasion of CCA cells.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the success of targeted therapy in colorectal, breast, lung cancer and melanoma, targeted treatment could be effective in advanced CCA, as well. However as frequency and distribution of the potentially actionable targets are exceptionally variable in CCA, comprehensive genomic testing seems to be a reasonable option before initiation of a targeted treatment (14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This recent genetic information has the potential to make precision medicine a part of routine clinical practice for the management of BTC patients [28].…”
Section: Discussionmentioning
confidence: 99%